2016
DOI: 10.1016/j.jshs.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

What do we know from clinical trials on exercise and Alzheimer's disease?

Abstract: Alzheimer’s disease (AD) is the most common form of dementia in elderly with major symptoms of a general term for memory loss and other intellectual abilities impairment which are serious enough to interfere with daily life. While there is no treatment can prevent and revise the cognitive function impairment in AD, physical activity becomes a potential beneficial intervention for AD. Multiple evidences suggested that exercise in general plays beneficial roles in improving brain function. Most common mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 13 publications
2
16
1
4
Order By: Relevance
“…However, one of the issues facing elderly's independent living is age-related cognitive decline (Ervin et al, 2012). This study was based on the support of literature for positive impact of intellectual exercise and training on the maintenance of cognitive abilities in elderly people (Fleiner et al, 2017;Öhman et al, 2016;Shen and Li, 2016). However, Vichitvanichphong et al (2017) believe that the existing adoption theories lack sufficient attention towards the context of empowering technologies such as cognitive training Xbox Kinects games, due in large part to the difficulty of the elderly for understanding the effectiveness or transfer effect of empowering technologies.…”
Section: Literature Support For Perceived Transfer Effect Of Cognitivmentioning
confidence: 99%
See 2 more Smart Citations
“…However, one of the issues facing elderly's independent living is age-related cognitive decline (Ervin et al, 2012). This study was based on the support of literature for positive impact of intellectual exercise and training on the maintenance of cognitive abilities in elderly people (Fleiner et al, 2017;Öhman et al, 2016;Shen and Li, 2016). However, Vichitvanichphong et al (2017) believe that the existing adoption theories lack sufficient attention towards the context of empowering technologies such as cognitive training Xbox Kinects games, due in large part to the difficulty of the elderly for understanding the effectiveness or transfer effect of empowering technologies.…”
Section: Literature Support For Perceived Transfer Effect Of Cognitivmentioning
confidence: 99%
“…There is a body of research on the positive impact of intellectual exercise and training on the maintenance of cognitive abilities in older age (Fleiner et al, 2017;Öhman et al, 2016;Shen and Li, 2016).…”
Section: Independent Livingmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that combined physical and cognitive activity improves or maintains cognitive and physical performance in older individuals diagnosed with mild cognitive impairment (MCI), especially the amnestic type [157]. Clinical trials on the effects of various exercises on the prevention of the AD suggested that long-term physical activity with a multicomponent cognitive intervention improves cognitive function in patients with AD [158]. Overall, the results imply that, after the onset of MCI or early AD, PE intervention alone may not be sufficient but still has the promise to improve function when combined with adequate cognitive activity.…”
Section: Physical Exercise For Modulating Aging and Preventing Dementiamentioning
confidence: 99%
“…In this special section, we invited 5 world-recognized clinical and basic scientists who specialize in AD studies to present the most recent discoveries: biomarkers for AD (Hampel et al. 1 ), the newest drug development (Vassar 2 ), potential anti-Tau therapy (Takashima 3 ), microbiome as a novel therapeutic approach (Lukiw 4 ), and exercise in the prevention of AD (Shen and Li 5 ).…”
mentioning
confidence: 99%